The Effect of Emotional Intelligence and Motivation on the Performance of Employees in the Personnel Maintenance Service of the Indonesian National Naval Headquarters - Aji Kusumajaya Nagara; Enjang Sudarman; Sukiman Sukiman (Dinasti Publisher, 2026)
This study aims to determine and analyze the influence of emotional intelligence on employee performance, the influence of motivation on employee performance, and the simultaneous influence of emotional intelligence and motivation on employee performance. The focus of this research was conducted on the Personnel Care Service of the Indonesian Navy Headquarters (Diswatpersal Mabesal), which is an important unit in maintaining security, public order, and personnel readiness. In the context of tasks that require emotional stability, mental toughness, and high motivation, these two variables are considered to have a strategic role in improving the quality of employee performance. This type of research uses a quantitative approach, where data is analyzed in numerical form to objectively test the relationship between variables. In addition, this study also utilizes qualitative data as support, in the form of statements in questionnaires, consultation results, and interviews with informants to enrich the interpretation of the research results. The population in this study amounted to 126 members of the Personnel Care Service of the Indonesian Navy Headquarters, and 96 respondents were selected as the research sample. Hypothesis testing was carried out using SPSS Version 29 software, which is able to analyze complex relationships between variables more accurately. The results of the study indicate that emotional intelligence (X1) and motivation (X2) have a positive and significant influence on employee performance (Y) partially. Meanwhile, the R-Square value of 0.401 or 40.1% indicates that employee performance can be explained by these two variables, while the remaining 59.9% is influenced by other factors not studied, thus opening opportunities for further research with broader variables